(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Escorted by the wide spread of Internet today, people have found a new way of expressing their opinions. It is a platform with a variety of information where an individual can also view the opinions of others. This is continuously growing and becoming an important factor in decision making for various organisations, businesses and even for Politics. In this paper we have chosen the most popular social media platform i.e. Twitter for our Sentiment Analysis. Eventually, Acknowledging the opinions beyond the tweets is of great concern. The fundamental aim of Sentiment Analysis is to reason feelings and ideas of individuals. We have made data analysis with tweets related to a topic and thereby classified their polarity using different machine learning algorithms.